Faktor Determinan Penggunaan Aplikasi Renal Data Processor dalam Meningkatkan Kualitas Layanan Hemodialisis di Rumah Sakit - Umi Khoirun Nisak; Irwan Alnarus Kautsar; Cholifah Cholifah (Jurnal Ners, 2025)
Healthcare services are rapidly evolving with the integration of information technology, including in hemodialysis services. This study aims to identify factors influencing the adoption of the renal data processor application in improving the quality of hemodialysis services at RS Siti Khodijah Sepanjang. Using a quantitative design with a survey method, data were collected from 135 respondents consisting of medical staff in the hemodialysis unit and other medical staff. Data analysis was performed using SmartPLS to test the structural model and the influence between variables. The results show that perceived threat significantly affects the coping strategies used by users, with R² values of 0.815 for coping 3, 0.618 for coping 1, and 0.768 for coping 2. Perceived threat increases the adoption of active and proactive coping strategies, while individual factors can reduce the perception of threat. This study emphasizes the importance of understanding the factors influencing the acceptance and use of the renal data processor application to optimize its benefits and address existing barriers.